Data-driven cluster analysis for identifying groups within users of anti-osteoporosis medication, using real-world primary care data. - Khalid, S; Ali, M; Silman, A; Prieto-Alhambra, D (International Society for Clinical Biostatistics, 2017)
Data-driven methods can be used for pattern recognition within a clinical population, enriching the existing analytical tools for clinical data analysis. We clustered anti-osteoporosis drug users with similar risk factors, to better determine the influence of therapy on their fracture risk